Initial findings using the V8 hourglass‐shaped valvuloplasty balloon for postdilatation in treating paravalvular leaks associated with transcatheter self‐expanding aortic valve prosthesis. Issue 7 (6th March 2016) - Latib, Azeem; Pedersen, Wesley; Maisano, Francesco; Lesser, John; Ruparelia, Neil; Figini, Filippo; Colombo, Antonio; Poulose, Anil; Kolbeck, James; Mooney, Michael; Schwartz, Robert; Youssef, Alicia; et al.
Abstract : Objectives: The aim of this study was to assess the effect of a novel hourglass‐shaped balloon on reduction of paravalvular leak (PVL) in patients undergoing transcatheter aortic valve replacement (TAVR) with self‐expanding prostheses. Background: An important limitation of TAVR compared with surgical aortic valve replacement remains the higher incidence of PVL. A commonly used strategy to treat PVL is balloon postdilatation (BPD); however, the optimal technique for treating PVL after TAVR is unknown. Methods: We examined consecutive patients with severe, symptomatic aortic stenosis who underwent TAVR with the Medtronic CoreValve followed by BPD with an InterValve V8 balloon for PVL grade ≥2+. Data from echocardiographic, multidetector computed tomographic, and angiographic images were reviewed. The primary endpoint was successful reduction in PVL to grade 1+ or less as assessed by intraprocedural echocardiography. Results: Eleven patients were studied (median age, 82 years; 64% female). Ten patients (91%) demonstrated successful reduction in PVL after V8 BPD. In three patients, PVL was reduced to zero or trace. PVL remained unchanged in one patient (2+). Two patients had complete heart block associated with valve deployment and received permanent pacemakers. There were no occurrences of annular injury or major adverse clinical events. Conclusions: BPD with the V8 hourglass‐shaped balloon was feasible in reducing PVL from self‐expanding TAVR prostheses. © 2016 Wiley Periodicals, Inc.